CSF Biomarkers of Amyloid and Tau Pathologies in Participants Enrolled in the Stanford Alzheimer's Disease Research Center. (20th December 2022) - Ramos Benitez, Javier A.; Wilson, Edward N.; Swarovski, Michelle S.; Shahid, Marian; Corso, Nicole; Channappa, Divya; Belnap, Malia; Tian, Lu; Kerchner, Geoffrey A.; Sha, Sharon; Henderson, Victor; Longo, Frank M.; et al.
Abstract: Background: Heterogeneity in the clinical presentation of Alzheimer's disease (AD) underscores the importance of biomarker‐defined diagnosis for use in medicine, research and clinical trials. Therefore, CSF measurement of amyloid and tau is an important tool in the diagnostic toolbox for inferring AD‐related brain pathologies. Because differences in preanalytical handling and in study population demographics render it difficult to apply a set of global concentration cut points for defining normal/abnormal for each analyte, it is critical that analyte cut points representing normal/abnormal be determined in a center‐specific manner. Method: This is a cross‐sectional analysis of CSF collected from participants enrolled in the ongoing prospective cohort study of the Stanford Alzheimer's Disease Research Center. Participants underwent lumbar puncture and cognitive evaluation to receive a diagnosis of cognitively unimpaired (CU), mild cognitive impairment (MCI) or AD. The current study included cognitively normal adults (n=78), individuals with MCI (n=36), and individuals with AD (n=26). Core CSF AD biomarkers p‐tau181, total tau, Aβ42 and Aβ40 were measured (Lumipulse G1200 platform, Fujirebio US, Inc). Cutpoints identifying normal/abnormal amyloid and tau were generated using the Youden method and Amyloid+ was defined as abnormally low CSF Aβ42/Aβ40 while Tau+ was defined as abnormally elevated CSF p‐tau181 and/or total tau. Result: Classification by amyloid and tau biomarkers revealed that in this population, 64.1% (n=50) CU were biomarker negative for tau or amyloid pathology. However, 28.2% (n=22) of the CU were Amyloid+, 5.1% (n=4) were Amyloid+ and Tau+, and 2.6% (n=2) were Tau+ alone. In the MCI diagnostic group, 33.3% (n=12) were Amyloid+ alone, while 30.6% (n=11) were both Amyloid+ and Tau+, and 5.6% (n=2) were Tau+ alone. 30.6% (n=11) were both Amyloid‐ and Tau‐. Within those receiving an AD diagnosis, 23.1% (n=6) had CSF biomarker evidence for being Amyloid+ only, 65.4% (n=17) were both Amyloid+ and Tau+, and 11.5% (n=3) participants had no biomarker evidence for Amyloid+ or Tau+. Conclusion: These results highlight the heterogeneity underlying amyloid and tau pathology in clinically defined diagnostic groups. Biomarker‐defined diagnosis using center‐specific cut points will support accurate diagnosis, treatment, clinical research and enrollment in clinical trials.